Application and progress of three‐dimensional bioprinting in spinal cord injury. Issue 4 (11th December 2021) - Xia, Qiu‐Qiu; Yuan, Hao; Wang, Ting‐Hua; Xiong, Liu‐Lin; Xin, Zhi‐Jun
Abstract: Spinal cord injury (SCI) is a central nervous system disorder that can lead to sensory and motor dysfunction, which can seriously increase pressure and economic burden on families and societies. The current SCI treatment is mainly to stabilize the spine, prevent secondary damage, and control inflammation. Drug treatment is limited to early, large‐scale use of steroids to reduce the effects of edema after SCI. In short, there is no direct treatment for SCI. Recent 3D bioprinting development provides a new solution for SCI treatment: a series of spinal cord bionic scaffolds are being developed to improve spinal cord function after injury. This paper reviews the pathophysiological characteristics of SCI, current treatment methods, and the progress of 3D bioprinting in SCI. Finally, its challenges and prospects in SCI treatment are summarized. Abstract : This paper reviews the pathophysiological characteristics of SCI, current treatment methods, and the progress of 3D bioprinting in SCI. Finally, its challenges and prospects in SCI treatment are summarized.